Automatic Disc Braking System Experimental Investigation - Karthick, A.; Prakash, L. (Asian Review of Mechanical Engineering, 2016)
The main objective of this project is for security system. If vehicle moves very near to the opposite vehicle then it applies brake automatically. It is used for avoiding accident over by racing in highways and parking or busy traffic areas through pneumatic braking. Pneumatic braking system works faster when compared to other devices. So we can achieve the high efficient operation by programming the microcontroller. The disc brake is a device for slowing or stopping the rotation of a wheel. Friction causes the disc and attached wheel to slow or stop. Brakes convert friction to heat, but if the brakes get too hot, they will cease to work because they cannot dissipate enough heat. This condition of failure is known as brake fade. Disc brakes are exposed to large thermal stresses during routine braking and extraordinary thermal stresses during hard braking.